Challenges and opportunities of freight forwarding industry in Bangladesh- An in-depth study of KUEHNE + NAGEL Bangladesh Ltd. (Sea-Export) - Tasnim, Bushra (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.